10.24843 The Variation of Sentence Structure in the Dyslexic Children’s Speech - Mulyono, Mulyono; Artawa, Ketut; Pastika, I Wayan; Subiyanto, Agus (e-Journal of Linguistics, 2018)
This study aims to describe the variation of sentence structure generated in the speech of dyslexic children. The design of this research is descriptive-qualitative with pospositivisme approach of interpretive phenomenology of naturalistic model. The research subjects were nine dyslexic children who used Indonesian as the first language and aged 8 to 10 years. The method used is listening and speaking method. In practice, the distributional method used by researcher are the IC technique. As an aid, the IC technique is supported by special techniques as an advanced techniques: Deletion, Substitution, Paraphrase, Perversion, and Expansion. From the research, it concluded that the Indonesian sentences produced by dyslexic children are dominated by incomplete sentences (59.61%), while complete sentences (40.39%) are the rest. Most complete sentences are basic sentences, while some are derivative sentences. From the basic sentence that appears, 38.66% basic sentence predicated verbs with the pattern of NP + VP, predicated noun patterned NP1 + NP2 with percentage 26.66%, predicated adjective with NP + AP pattern of 23.55%, predicate the preposition patterned NP + PP of 5.78%, and the last predicate numeral with NP + NumP pattern of 4.88%. The derivation sentence is dominated by single sentence with percentage value 97,62%, compound sentence equal to 0,44%, and multi-story sentence equal to 1,94%. The incomplete sentences conveyed by DC consist of the SUBJ only structure pattern, PRED only, OBJ only, ADJ only, or combined functions of SUBJ-OBJ, SUBJ-ADJ, PRED-OBJ, PRED-ADJ, and PRED-OBJ-ADJ.